THE BACTERIAL FLORA, TRIMETHYLAMINE AND TOTAL VOLATILE NITROGEN OF FISH MUSCLE AT 0Â° C. (IN ICE) - Velankar, N K; Kamasastri, P V (Indian Journal of Fisheries, 2015)
Observations on the changes occurring in the bacterial flora and the trimethylamine and total volatile nitrogen content of fish muscle at 3Â° C. were reported previously (Velankar, 1956). The results of similar studies on fish kept in ice storage are presented in this paper and the bacterial flora, isolated during these investigations, is described.